El marketing emocional y la fidelización del cliente. Análisis a partir de los componentes emocionales del Modelo Value Star en la banca por internet del BCP - Tocas Santos, César Augusto (2018)
The aim of this study is to present the relationship between the emotional components defined from the Value Star Model of emotional marketing and customer loyalty, focusing on the Internet banking channel at Banco de Crédito del Perú (BCP). The definition of customer loyalty and emotional marketing is presented, pointing out, then, the importance of the latter to achieve one of the main strategic objectives of the organizations that is the loyalty of their clients. From the methodological point of view, the research had a mixed approach, correlational scope, gathering information through surveys, in-depth interviews and digital observations. Likewise, structural equations were used to validate if the items allow measuring the variables of the emotional components that are proposed as part of the proposed model: Value Star. In the findings it was possible to demonstrate that the BCP uses the emotional marketing strategy in Internet banking to achieve customer loyalty. Finally, the conclusions and limitations of our researchare presented.